1999
DOI: 10.1159/000012031
|View full text |Cite
|
Sign up to set email alerts
|

Infusions of Fluorouracil and Leucovorin: Effects of the Timing and Semi-Intermittency of Drug Delivery

Abstract: Preclinical and clinical studies have demonstrated that the circadian modulation of 5-FU delivery may reduce toxicities and improve antitumor activity. However, the relative importance of the timing of 5-FU delivery has not been clinically addressed. The aims of this study were to determine the toxicities, the maximum tolerable doses and the activity of a regimen with 5-fluorouracil (5-FU) and leucovorin (LV) administered as a 14-day continuous infusion according to a flat or three different chronomodulated rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Our model is consistent with these findings, and indicates that higher total doses of chronomodulated drug can be tolerated and are needed to achieve the same anti-tumor efficacy. These theoretical results are in agreement with clinical trials that showed consistent higher tolerance for chronomodulated compared to constant infusion [4], even when given at non-optimal times [24]. Lesser toxicity is independent from the circadian rhythms, i.e.…”
Section: Resultssupporting
confidence: 88%
“…Our model is consistent with these findings, and indicates that higher total doses of chronomodulated drug can be tolerated and are needed to achieve the same anti-tumor efficacy. These theoretical results are in agreement with clinical trials that showed consistent higher tolerance for chronomodulated compared to constant infusion [4], even when given at non-optimal times [24]. Lesser toxicity is independent from the circadian rhythms, i.e.…”
Section: Resultssupporting
confidence: 88%
“…Another explanation is that ORR may be influenced by drug flow rate instead of setting peak delivery . Chrono‐chemotherapy of 5‐FU follows a peak delivery time of 4:00 a.m . This shows drug flow rate may be a robust determinant for ORR.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, data on human circadian DPD expression and activity pattern are circumstantial. Nevertheless, extensive studies comparing different regimens of 5-FU cancer chemotherapy have shown a significantly better tolerability of 5-FU when it was administered in a chronomodulated manner (Levi et al 1997;Falcone et al 1999;Giacchetti et al 2000). Probably mechanisms different from circadian DPD rhythms are responsible for the better tolerability of chronomodulated 5-FU chemotherapy.…”
Section: Discussionmentioning
confidence: 99%